Process-structure-properties in polymer additive manufacturing via material extrusion : a review - Goh, Guo Dong (2020)
This article provides a database of the mechanical properties of additively manufactured polymeric materials fabricated using material extrusion (e.g., fused filament fabrication (FFF)). Mechanical properties available in the literatures are consolidated in table form for different polymeric materials for FFF. Mechanical properties such as tensile, compressive, flexural, interlayer, fatigue, and creep properties are discussed in detail. The effects of printing parameters such as raster angle, infill, and specimen orientation on properties are also provided, together with a discussion of the possible causes (e.g., texture, microstructure changes, and defects) of anisotropy in properties. In addition to that, research gaps are identified which warrant further investigation.